Einstein's misgivings about his 1905 formulation of special relativity - Brown, H (Institute of Physics Publishing, 2005)
When Einstein formulated his 1905 treatment of relativistic kinematics, the template in his mind was thermodynamics. This was because a more desirable 'constructive' account of the behaviour of moving rods and clocks, based on the detailed physics governing their microscopic constitution, was unavailable. The price to be paid was appreciated by Einstein and a handful of others since 1905. "The principal of relativity is a principle that narrows the possibilities; it is not a model, just as the second law of thermodynamics is not a model." Albert Einstein.